Understanding foot conditions, morphologies and functions in children: a current review - Jiang, Hanhui; Mei, Qichang; Wang, Yuan; He, Junhao; Shao, Enze; Fernandez, Justin; Gu, Yaodong (Frontiers in Bioengineering and Biotechnology, 2023)
This study provided a comprehensive updated review of the biological aspects of children foot morphology across different ages, sex, and weight, aiming to reveal the patterns of normal and pathological changes in children feet during growth and development. This review article comprised 25 papers in total that satisfied the screening standards. The aim was to investigate how weight changes, age and sex affect foot type, and gain a deeper understanding of the prevalent foot deformities that occur during children growth. Three different foot morphological conditions were discussed, specifically including the effect of sex and age differences, the effect of weight changes, and abnormal foot morphologies commonly documented during growth. This review found that sex, age, and weight changes would affect foot size, bony structure, foot posture, and plantar pressures during child growth. As a result of this biological nature, the children's feet generally exhibit neutral and internally rotated foot postures, which frequently lead to abnormal foot morphologies (e.g., flat foot, pronated foot, etc.). In the future, attention shall be paid to the causal factors leading to specific foot morphologies during the growth and development of children. However, sufficient evidence could not be provided due to a relatively short period of investigation and non-uniformed research methodology in the current literature. A more comprehensive and in-depth exploration is recommended to provide scientific evidence for the discovery of children foot development and personalized growth pattern.